2010
DOI: 10.1089/tmj.2010.0034
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance 12-Lead Electrocardiography Transmission via Cell Phone Technology to Cardiologists

Abstract: This study demonstrates transmission of 12-lead electrocardiography (ECG) in an ambulance to the cell phone of the attendant emergency medical technician and then to the hospital and to cell phones of off-site cardiologists. The emergency medical technician cell phone receives Extensible Markup Language files generated by a Phillips Extensible Markup Language ECG instrument via Wi-Fi-based wireless network and then sends them to an ECG-processing server at the hospital over the mobile telephone network. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…In ambulances, they may assist the monitoring and decision making in severely ill patients 13,14 and provide excellent service to patients with severe decompensated heart disease, even when the procedure is performed by paramedics or other health professionals 15 .…”
mentioning
confidence: 99%
“…In ambulances, they may assist the monitoring and decision making in severely ill patients 13,14 and provide excellent service to patients with severe decompensated heart disease, even when the procedure is performed by paramedics or other health professionals 15 .…”
mentioning
confidence: 99%
“…The interventions are described in Multimedia Appendices 8 and 9. Interventions using mobile communication technologies in both developed countries (Italy [205], US [1,92,206-228], UK [229-232], France [233], Canada [234-237], Japan [238], Australia [239], New Zealand [240], South Korea [241-245], and Denmark [246]), and developing ones (Thailand [247], Peru [248], Kenya [57,249,250], Taiwan [251,252], Israel [253-255], Uganda [256,257], Thailand [258], Singapore [259], Turkey [260], India [261], and South Africa [262]) have investigated the use of mobile phone-based apps, mobile phone voice call, SMS, and PDAs.…”
Section: Resultsmentioning
confidence: 99%
“…The video function was used to send reminders to assist with daily activities of persons with early dementia [230], and transmit teleconsultations, including clinical images of the amputated portion and stump as well as patient information between the physicians in the emergency room and the consultant plastic surgeon through Panasonic camera phones [251]. In addition, transmitting the 12-lead electrocardiography in an ambulance to the cell phone of the attendant emergency medical technician and then to the hospital and to cell phones of off-site cardiologists [252]. SMS was used to deliver diet, exercise, and behavior modification once a week to obese patients [241].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that ECG images, which are not bandwidth intensive, can be efficiently transferred by cell phone for cardiologists to review. 36,37 In contrast, cell phone transmission of arthroscopic videos was error prone because the bit rate was only 55 Kbps and resolution was only 176 · 144 pixels. Although 95% of the pathologies could be diagnosed, the technology was inadequate for teleconsultation because of transmission latencies and interruptions and because correct anatomical orientation was identified only 60% of the time.…”
Section: Recent Studiesmentioning
confidence: 99%
“…Even higher transmission quality may be insufficient for diagnosing certain problems, such as eye conditions with micro-movement, as was the case with the standard-definition video transmitted at 384 Kbps, the highest transmission rate commonly available at the time the study was done. 13 Current cell phone technology, however, can accommodate the low bandwidth requirements of ECG transmission, 36,37 but not the higher ones for transmitting arthroscopic videos. 38 …”
mentioning
confidence: 99%